SISTEM DESKRIPTOR TANPA KETERKONTROLAN TAK HINGGA - Hasbiyati, Ihda
Abstract : This paper concerns the stucture that can be achieved by feedback in descriptor systems that lack controllability at infinity. Ex = Ax + Bu, where E, A and B are complex matrices, but E is a singuler ma-trice, Staircase condensed forms for the system obtained through a sequence of orthogonal state transformations display when and how feedback can be used to achieve minimal index.